Differences in physicochemical properties and proteomics analysis of spray- and freeze-dried milk powders from bovine, goat, and horse sources - Shichu Zhou; Xin Zhang; Junyu Zhang; Changjiang Zang; Rongbo Fan; Jun Wang; Tongjun Guo; Rongwei Han; Yongxin Yang (Journal of Dairy Science)
ABSTRACT: Milk powder, a nutrient-rich dairy product, lacks comprehensive information summarizing its specific properties when produced by spray- and freeze-dried technologies from different sources. Therefore, this study investigated the differences in physicochemical properties, microstructure, and proteome of spray- and freeze-dried milk powders from bovine, goat, and horse sources. The results revealed that spray-dried milk powder exhibited a smaller particle size, lower air content within the powder particles, inferior reconstitution properties, and lower lactose crystallinity compared with freeze-dried milk powder. Additionally, among the studied varieties, horse milk powder showed the lowest flowability but the most effective reconstitution properties. Proteomic analysis indicated that freeze-dried milk powder exhibited higher levels of immune-related proteins, including complement C3, C7, and complement factor B, and antimicrobial enzymes such as lysozyme and lactoperoxidase compared with spray-dried milk powder. Furthermore, specific milk powders contained more immune-related proteins such as serum amyloid A, myeloid antimicrobial peptide-28, polymeric immunoglobulin receptor, and mucin-1 compared with bovine milk powder. These findings contribute to a deeper understanding of the differences in the physicochemical properties and potential biological functions of spray- and freeze-dried milk powders from various sources, which may help in further optimizing specific milk powder processing technologies.